Incidence of Symptomatic Internal Hernia following Minimal Invasive colorectal surgery: A Single Center Experience - Nakarmi, Rajiv; Yu-Feng, Tian; Ong, Khaa-Hoo; Shrestha, Muza; Maharjan, Sundar; Chhetri, Suman Bikram Adhikari (Nepal Medical College Journal, 2021)
Laparoscopy has been adopted in the surgical specialties and colorectal surgery for treatment of benign and malignant diseases. Recent reviews suggest that the incidence of symptomatic internal hernias after laparoscopic colorectal resection is from 0.39 to 0.65%. Unlike in open surgery, laparoscopic closure of a mesenteric defect is inherently challenging as inadvertent injury to the marginal vessels may compromise blood supply to the anastomosis. For these reasons, many surgeons leave the defect open during laparoscopic surgery. But this may lead to development of post-operative internal hernia through the defect. This is a retrospective study where we included 149 patients who underwent laparoscopic/ robotic colorectal surgeries from March 2019 to March 2020. Data pertaining for following variables were collected which included age, sex, indication for surgery, location of the pathology, splenic flexure mobilization. The incidence of internal hernia among these patients were calculated and assessed using SPSS 20. Incidence of internal hernia was found to be 0.67% which was diagnosed and treated on the 18th post-operative day of initial surgery. Internal hernia is a rare but important complication of laparoscopic/robotic colorectal surgery with a high mortality rate if not diagnosed early. Defect closure is still controversial during the initial surgery and probably not indicated for all patients and depends on surgeon’s preference.